Persepsi Perbandingan Keunggulan Pembiayaan Mudharabah Dan Murabahah Oleh Nasabah Lembaga Keuangan Mikro Islam BMT - Azhar Alam; Sanitra Septiana; Afief El Asfahany; Raisa Aribatul Hamidah (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
This study aims to explore perceptions of the comparative advantage of mudharabah and murabahah financing from the customer side of Islamic microfinance institutions. This study uses an approach using field data in the case study of BMT Alfa Dinar, Karanganyar, Central Java, Indonesia. The data in this study were obtained from 10 customers or customers of murabahah and mudharabah financing, which were taken directly using observation, question and answer, and documentation techniques. The collected data is then analyzed in terms of content, abstracted, and presented. The results of this study are that customers have different perceptions about the advantages of mudharabah and murabahah financing. This perception is seen from various perspectives, including risk, margin, transparency period, and work system. Mudharabah has the advantage of being more reliable than Murabaha. Meanwhile, Murabaha has the advantage of fixed profits or tends to be stable, and if agreed, it cannot be changed. This Murabaha contract is different from the mudharabah, whose profits tend to be unstable. This study recommends increasing business management literacy with mudharabah contract financing to maximize the benefits of Islamic microfinance institutions and customers.